2017
DOI: 10.3389/fpubh.2017.00219
|View full text |Cite
|
Sign up to set email alerts
|

Computer Vision Malaria Diagnostic Systems—Progress and Prospects

Abstract: Accurate malaria diagnosis is critical to prevent malaria fatalities, curb overuse of antimalarial drugs, and promote appropriate management of other causes of fever. While several diagnostic tests exist, the need for a rapid and highly accurate malaria assay remains. Microscopy and rapid diagnostic tests are the main diagnostic modalities available, yet they can demonstrate poor performance and accuracy. Automated microscopy platforms have the potential to significantly improve and standardize malaria diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The results of one-way sensitivity analysis also indicated that RDT would dominate microscopy in other specific scenarios, such as, when the proficiency of laboratory personnel decreased, and salary increased. Than the image recognition based on artificial intelligence is likely to reduce labor costs and maintain the accuracy of microscopy [34,35]. But for now, it was difficult to for microscopy to have a higher sensitivity compared to RDT.…”
Section: Discussionmentioning
confidence: 99%
“…The results of one-way sensitivity analysis also indicated that RDT would dominate microscopy in other specific scenarios, such as, when the proficiency of laboratory personnel decreased, and salary increased. Than the image recognition based on artificial intelligence is likely to reduce labor costs and maintain the accuracy of microscopy [34,35]. But for now, it was difficult to for microscopy to have a higher sensitivity compared to RDT.…”
Section: Discussionmentioning
confidence: 99%
“…The results of one-way sensitivity analysis also indicated that RDT would dominate microscopy in other specific scenarios, such as, when the proficiency of laboratory personnel decreased, and salary increased. Than the image recognition based on artificial intelligence is likely to reduce labor costs and maintain the accuracy of microscopy [33,34]. But for now, it was difficult to for microscopy to have a higher sensitivity compared to RDT.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more and more targets for detection on diagnostic chips have been investigated. Some salient examples thereof are circulating tumor cells (CTC) of various types of cancer [1,[36][37][38], rare cells (e.g., sickle-cell variants of red blood cells) [39,40], parasites, like Plasmodium falciparum [1,7,10,11,[13][14][15][21][22][23]36,[41][42][43][44][45][46][47][48][49][50] and Trypanosoma spp. [8,44,[51][52][53][54][55][56][57] and even plant pathogens [26,58], as well as-after cells have been lysed-subcellular infection markers (e.g., DNA, RNA fragments) [10,11,22,43,[59][60][61][62].…”
Section: What We Can Detectmentioning
confidence: 99%